2022
DOI: 10.4254/wjh.v14.i3.551
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of hypothyroidism and effect of thyroid hormone replacement therapy in patients with non-alcoholic fatty liver disease: A population-based study

Abstract: BACKGROUND Non-alcoholic fatty liver disease (NAFLD) is currently considered as the most common cause of chronic liver disease worldwide. Risk factors for NAFLD have been well-described, including obesity, type 2 diabetes mellites (T2DM), dyslipidemia (DLP) and metabolic syndrome. Hypothyroidism has been identified as an independent risk factor for the development of NAFLD, although the literature is inconsistent AIM To evaluate the prevalence of hypothyroidism in patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Moreover, our study is limited by the fact that the definition of NASH and GDM could have been heterogeneous across different United States centers. Despite its limitations, Explorys platform has been validated as a database in several different fields including gastroenterology and endocrinology 11,12,24–26 . It is also an excellent research tool that provides clinicians with fruitful resources to investigate disease epidemiology and burden on a large population scale.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, our study is limited by the fact that the definition of NASH and GDM could have been heterogeneous across different United States centers. Despite its limitations, Explorys platform has been validated as a database in several different fields including gastroenterology and endocrinology 11,12,24–26 . It is also an excellent research tool that provides clinicians with fruitful resources to investigate disease epidemiology and burden on a large population scale.…”
Section: Discussionmentioning
confidence: 99%
“…Despite its limitations, Explorys platform has been validated as a database in several different fields including gastroenterology and endocrinology. 11,12,[24][25][26] It is also an excellent research tool that provides clinicians with fruitful resources to investigate disease epidemiology and burden on a large population scale.…”
Section: Discussionmentioning
confidence: 99%
“…In the Third National Health and Nutrition Examination Survey (NHANES III), Fan and his colleagues found that BMI and ALT partially mediated the association between TSH and NAFLD (Fan et al, 2022). There is evidence that individuals with high levels of TSH, especially those diagnosed with hypothyroidism, are more likely to develop NAFLD (Almomani et al, 2022; Fan et al, 2022). In our study, BMI was an independent risk factor for thyroiditis.…”
Section: Discussionmentioning
confidence: 99%
“…Access to the database is granted to participating healthcare systems. The use of the Explorys platform has been validated in multiple fields, including gastroenterology and endocrinology [ 24 , 25 ].…”
Section: Methodsmentioning
confidence: 99%